2016
DOI: 10.1111/vox.12432
|View full text |Cite
|
Sign up to set email alerts
|

The experience of extended blood group genotyping by next‐generation sequencing (NGS): investigation of patients with sickle‐cell disease

Abstract: Overall, we consider that our strategy for NGS-based EBGG, assisted by a simple method for genotyping exons 1 and 2 of the pairs of homologous genes (i.e. RHD/RHCE and GYPA/GYPB), as well as the future support of potent bioinformatics tools, may be implemented for routine diagnosis in specific populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 33 publications
0
38
0
3
Order By: Relevance
“…Distinguishing neutral passenger variants from deleterious mutations has challenged genomics from its inception, and as NGS is applied to transfusion medicine, novel blood group variants have been a recurrent finding . Several prediction tools used widely in genomics have not been tested for immunohematology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Distinguishing neutral passenger variants from deleterious mutations has challenged genomics from its inception, and as NGS is applied to transfusion medicine, novel blood group variants have been a recurrent finding . Several prediction tools used widely in genomics have not been tested for immunohematology.…”
Section: Discussionmentioning
confidence: 99%
“…A number of successful clinical applications have been reported, and further efforts are under way in the areas of oncology, hemostasis, obstetrics, and pharmacology to identify the clinical benefits of genomic medicine . Transfusion medicine is an additional discipline with a strong genetics foundation that is exploring this approach …”
mentioning
confidence: 99%
“…The inherent “personalized” nature of selecting the best blood product for each patient, along with the breadth of genomic information potentially relevant for transfusion therapy (e.g., red blood cells [RBCs], platelets [PLTs], neutrophil antigens, and HLA) and the documented clinical value, make transfusion medicine an ideal field for the use of NGS or MPS data. A number of publications over the past 6 years have provided sound proof‐of‐principle examples of the application of targeted (sequencing specific genes), exome (sequencing the coding regions only), or whole genome (sequencing both coding and noncoding regions) NGS to determine the extended RBC, PLT, RH, or HLA profiles of patients or donors …”
Section: Ngs or Mps Approachesmentioning
confidence: 99%
“…A recent proof‐of‐principle study demonstrated the capability of using whole genome sequencing data for comprehensive antigen prediction of RBCs and platelets . A targeted exome sequencing approach has been recognized for its utility in blood group genotyping and has been predicted to facilitate investigation of novel blood group alleles . While studies have shown proof of principle for blood group genotyping by MPS, no studies have investigated to date its clinical application to resolve complex cases in a reference laboratory setting …”
mentioning
confidence: 99%